Deciphering the concurrent phenomenon of childhood malnutrition by using the extended composite index of anthropometric failure (ECIAF): facts from the BESLEN project - Gözde Dumlu Bilgin; İrem Kaya Cebioğlu; Hasan Kaan Kavsara; Aybüke Sarioğlu; Melis Keküllüoğlu Tan; Sema Aydin; Pınar Usta; Binnur Okan Bakir (Public Health Nutrition)
Abstract